Aborsi Dalam Perspektif Fiqih - Khilmi, Slamet (Musawa Jurnal Studi Gender dan Islam, 2003)
Islam has a deep respect for human life, and as such abortion is basically forbidden in Islam. Experts in Islamic law agree that abortion conducted after the foetus is considered to have a soul (after 4 months or 120 days) is forbidden. Nevertheless, Islamic scholars have different opinions in cases where the foetus does not yet have a soul; some permit it, and some forbid it. Those experts in Islamic law who allow it include lbnu 'Abidi from the Hanafi school and lbnu Qudamah from the Hambali school. Meanwhile, those who forbid it include Imam al-Gazali from the Syafi'i school. The writer of this article tends toward the opinion that forbids abortion even when the foetus does not yet have a soul. Nevertheless he does believe that a person may have an abortion in an emergency situation such as to save the life of the mother.